161k views
5 votes
What is the answer to F(x)=6+3x

User Saner
by
6.1k points

1 Answer

0 votes

(F)=6+3F

We move all terms to the left:

(F)-(6+3F)=0

We add all the numbers together, and all the variables

F-(3F+6)=0

We get rid of parentheses

F-3F-6=0

We add all the numbers together, and all the variables

-2F-6=0

We move all terms containing F to the left, all other terms to the right

-2F=6

F=6/-2

F=-3

I don’t know if it is right but I hope this helps :)
User Robin Rizvi
by
5.6k points